2020
DOI: 10.3390/pathogens9110908
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted Epidemiological Patterns of West Nile Virus Lineages 1 and 2 Infections in France from 2015 to 2019

Abstract: Since 2015, annual West Nile virus (WNV) outbreaks of varying intensities have been reported in France. Recent intensification of enzootic WNV circulation was observed in the South of France with most horse cases detected in 2015 (n = 49), 2018 (n = 13), and 2019 (n = 13). A WNV lineage 1 strain was isolated from a horse suffering from West Nile neuro-invasive disease (WNND) during the 2015 episode in the Camargue area. A breaking point in WNV epidemiology was achieved in 2018, when WNV lineage 2 emerged in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 65 publications
4
66
1
Order By: Relevance
“…Arboviruses are emerging pathogens on the European continent and, more generally worldwide, although they are already well established in various regions, particularly in Africa and Latin America. Among arboviruses, several flaviviruses (Flaviviridae family), e.g West Nile (WNV), Usutu (USUV), tick born encephalitis virus (TBEV), and Meaban (MEAV) viruses are the main flaviviruses that have been known to circulate in France [1][2][3][4]. WNV and USUV belong to the Japanese encephalitis (JEV) serocomplex in the Flavivirus genus and share many common features [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Arboviruses are emerging pathogens on the European continent and, more generally worldwide, although they are already well established in various regions, particularly in Africa and Latin America. Among arboviruses, several flaviviruses (Flaviviridae family), e.g West Nile (WNV), Usutu (USUV), tick born encephalitis virus (TBEV), and Meaban (MEAV) viruses are the main flaviviruses that have been known to circulate in France [1][2][3][4]. WNV and USUV belong to the Japanese encephalitis (JEV) serocomplex in the Flavivirus genus and share many common features [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We succeeded at sequencing a 341 bp WNV genomic region (GenBank accession number OK489805) located on the envelope gene on one excreta sample that was tested positive by RT-qPCR with the lowest Ct (sample F 2020/09/15). Phylogenetic analysis revealed that the WNV identified in our study belonged to lineage 1 and was closely genetically related to a WNV isolated on a symptomatic horse the 3 rd of October 2015 13 (GenBank accession number MT863559) (Figure 3 A). Our WNV small genomic section diverged from the 2015 WNV (GenBank accession number MT863559) by 5 single nucleotide polymorphism (SNPs) and from a WNV isolated in Spain on a horse in 2010 14 (GenBank accession number JF719069) by 4 SNP (Figure 3 B).…”
Section: Virus Screening In Mosquito Excretamentioning
confidence: 75%
“…One of the largest outbreaks was reported in Romania in 1996 and 1997, with more than 500 clinical cases in humans with almost 10% mortality [ 12 ]. Since 2015, annual WNV outbreaks of varying intensities in wild animals have been reported in France [ 13 ]. In 2018, a dramatic increase in WNV infections in people and animals was reported across Europe, with the most cases in Italy, Serbia, and Greece [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, there were 2083 cases of WNV outbreaks in humans and 285 outbreaks among equids from 1999 to 2019 [ 14 ]. Initially, WNV lineage 1 was identified as a cause of human outbreaks across Europe, whereas WNV lineage 2 was introduced in Europe later, in 2004, and then dispersed to eastern Austria and other European countries as a major prevalent strain [ 13 ]. In 2018, WNV lineage 2 appeared in southeastern Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation